THE EFFECT OF WORK ENVIRONMENT AND MOTIVATION ON EMPLOYEE PERFORMANCE OF PT. HASTA MULTI SEJAHTERA CIKARANG - Yuan Badrianto; Muhamad Ekhsan (Kusuma Negara Business School, 2019)
Work environment and motivation are two of the factors that are thought to be relatively large in influencing employee performance at PT Hasta Multi Sejahtera. To prove the influence of both of them, this study was conducted to determine the effect of the work environment and motivation on performance at PT Hasta Multi Sejahtera. The study was conducted at PT Hasta Multi Sejahtera Cikarang by taking 60 respondents, as a sample in the study for 3 months. Data retrieval is done by using a Likert scale questionnaire, and by using a quantitative descriptive approach. Therefore, the analysis of the data used is statistical analysis in the form of multiple linear regression tests. The results of this study indicate that partially and simultaneously work environment and motivation variables influence the performance of employees at PT Hasta Multi Sejahtera Cikarang. This is evidenced by the results of the simultaneous test (F test) and the results of the partial test (t-test) also show the significant value of the two independent variables that support the hypothesis. Therefore the test results of this study state that there is a simultaneous influence between work environment variables and motivation on employee performance at PT Hasta Multi Sejahtera